If You Give a Mouse a Cookie - Numeroff Laura Joffe; Nang ChanYeema (New York, USA Scholastic Inc., 1985)
If you give a mouse a cookie, he's going to ask for a glass of milk...and that's only the beginning!
Keywords: Story Collection